Clinical Practice Guidelines: Incorporating Input From a Patient Panel. Issue 8 (16th June 2017) - Goodman, Susan M.; Miller, Amy S.; Turgunbaev, Marat; Guyatt, Gordon; Yates, Adolph; Springer, Bryan; Singh, Jasvinder A.
Abstract : Objective: To describe the integral role of a Patient Panel in the development of the 2017 American College of Rheumatology (ACR)/American Association of Hip and Knee Surgeons (AAHKS) clinical practice guideline. Methods: We convened a Panel of 11 patients with rheumatoid arthritis and juvenile idiopathic arthritis, all of whom had undergone 1 or more arthroplasties, to review the evidence and provide guidance on recommendations for the 2017 ACR/AAHKS guideline to address the perioperative management of antirheumatic medication in patients with rheumatic diseases undergoing elective total hip or total knee arthroplasty. The guideline used the Grading of Recommendations Assessment, Development, and Evaluation methodology that acknowledges the critical role of patient values and preferences when the quality of the evidence base is low or when there are important trade‐offs between benefits and harms. The Patient Panel considered the relative importance of complications including perioperative infection versus rheumatic disease flare and voted on the recommendations. Before the Voting Panel's own discussion of the recommendations, they reviewed a summary of the Patient Panel's discussion, including their perioperative experience, the relative importance they placed on infections versus flares in the perioperative period, and their votes on the recommendations. Results: The Patient Panel placed higher importance on avoiding an infection than a disease flare despite the far greater frequency of flares than infections. The decisions of the Voting Panel were concordant with those of the Patient Panel. For the 7 recommendations that both Panels voted on, the Panels agreed on the direction as well as the strength of recommendation (which was conditional for all recommendations). Conclusion: The Voting Panel considered the importance that the patients placed on risk of infection. The Patient Panel's values informed the direction and strength of the recommendations in the final 2017 ACR/AAHKS guideline.